Licensing Socialization, Digital Marketing and MSME Bookkeeping Workshop for Retired Migrant Workers In Pagak Village Purwareja Klampok District Banjarnegara Regency - Mirna Dyah Praptitorini; Anis Turmudhi; Noor Salim; Rahul Bhandari; Muhamad Saufi Che Rusuli; Marlon Rael Astillero; Benediktus Ardie Reho; Siti Shobandiyah (Jurnal Pengabdian Masyarakat Nusantara, 2022)
MSMEs need to provide opportunities for local entrepreneurs and utilize local resources to help stimulate economic activity and increase the competitiveness of a region as a whole. Based on the problems mentioned above, it is necessary to hold training on the use of digital marketing tools and socialize the processing of business permits for micro, small and medium enterprises (MSMEs) in Pagak Village, Banjarnegara Regency as a solution. In the socialization process, an MSME association was also formed whose members were active in the business world in Pagak Village. All presenters have tried to provide all the knowledge about the digital marketing and bookkeeping process for MSMEs and various interesting things regarding business licensing, so it is hoped that the entrepreneurial knowledge provided can be directly applied by the MSME community, especially in Pagak Village.